PROJECT FIGHT 2 - Development of an Edible Bait Vaccine to Control Rabbit Haemorrhagic Disease Virus 2 (RHDV2) in Wild Rabbits - Carvalho, CL (2019)
PROJECT FIGHT-TWO - EDIBLE BAIT VACCINE FOR RABBIT HAEMORRHAGIC DISEASE VIRUS 2 (RHDV2) CONTROL IN WILD RABBITS Carina L. Carvalho1,2, Madalena Monteiro1, Paulo Carvalho1, Paula Mendonça1, Jorge Correia3, Berta São Brás, Conceição Peleteiro 2, Elsa Duarte3, António Mira3, Sandra Branco 3, António Roldão4, Margarida D. Duarte1,2 1-Instituto Nacional de Investigação Agrária e Veterinária Av. da República, Quinta do Marquês 2780-157 Oeiras 2-ICAAM – Instituto de Ciências Agrárias e Ambientais Mediterrânicas, Instituto de Formação e Investigação Avançada, Universidade de Évora. Pólo da Mitra, Ap. 94, 7006-554 Évora 3-CIISA, Faculdade de Medicina Veterinária, Universidade de Lisboa, Avenida da Universidade Técnica, 1300-477 Lisboa 4- IBET – Instituto de Biologia Experimental e Tecnológica, Avenida da República, Estação Agronómica, 2780-157 Oeiras Rabbit haemorrhagic disease (RHD) is a highly contagious and often lethal systemic infection in the European rabbit (Oryctolagus cuniculus). Presently, the condition is caused by the rabbit haemorrhagic disease virus 2 (RHDV2), which replaced the classical RHDV genogroups (G1-G6) after its emergence in 2010, and continues to cause great concerns on the conservation of the diminished Iberian wild rabbit populations, directly impacting on several endangered species that depend on the rabbit for survival. The commercial RHDV2 vaccines available to date are inactivated, obtained from infected animal liver extracts and the route of administration is usually subcutaneous, requiring handling. Further than the risks associated with incomplete virus inactivation and the inadvertent release of infectious virus, these vaccines are not suitable for wild rabbits, requiring capture for inoculation. The immunity is short and, hence, the protection transient. The previous commercial RHDV vaccines, most also inactivated, were shown to be ineffective in conferring cross protection against RHDV2. The FIGHT-TWO strategic framework is the development and production of a new edible vaccine against RHDV2 which is presently disseminated in the entire territory of Portugal, including the insular regions. The safe, pathogen-free RHDV2 oral vaccine is to be distributed in the field as bait or included in dry feed. This non-invasive immunization has the potential to protect a broad proportion of the populations, crucial to stop virus transmission and control the infection, while overcoming the need of capture and manipulation. The virus-like particle (VLP)-based vaccine will be produced in insect cells-baculovirus expression vector system (IC-BEVS) and updated accordingly to RHDV2 evolution (open system). To accomplish FIGHT-TWO objectives, INIAV, the reference laboratory for animal diseases, join forces with IBET, UE and FMV. FIGHT-TWO will allow to proceed with one of the 12 measures specified in the Action Plan for the Control of Rabbit Hemorrhagic Viral disease in Rabbits (Dispatch 4757/17 of 31 May). Obtaining this vaccine will be crucial to support more generalist wild rabbit management policies towards the recovery of population densities and disease control, the recovery of ecosystems where the rabbit is keystone and the reactivation of hunting activities in Portugal. Keywords (max: 6): Oryctoalgus cuniculus algirus, wild rabbit, RHDV2, oral vaccine, VP60-VLPs, Acknowledgments: PTDC/CVT-CVT/29062/2017-PT2020; Partnership +Coelho